PENGARUH EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) TERHADAP PERILAKU PENCEGAHAN COVID-19 PADA ANAK USIA SEKOLAH - Sri Aminingsih; Endang Dwi Ningsih (KOSALA : Jurnal Ilmu Kesehatan, 2022)
Background. According to the Ministry of Health of the Republic of Indonesia (2020), the age group of children is very vulnerable to being infected with COVID-19. Classification of children aged less than 18 years with a total number of children as many as 79.5 million or 30.1% of confirmed cases of positive COVID-19 children. The percentage is 8,1% positive for COVID-19, 8,6% being treated, 8,3% recovering, and 1,6% dying. In an effort to maintain the health of children, the Indonesian Ministry of Health has determined several preventions for COVID-19, which include implementing a clean and healthy lifestyle (washing hands with soap, using a mask when coughing or colds, exercising regularly, getting enough rest and consuming a balanced diet with lots of vegetables and fruits). fruit). A clean and healthy lifestyle must be applied as early as possible so that it becomes a positive habit in maintaining health. SDN 01 Malanggaten is a public elementary school located in the east of the Kebakramat sub-district. The number of students from grades 4 to 6 is approximately 60 students. Based on information from the Indonesian Ministry of Health (2020), school-age children are very vulnerable to COVID-19, so it is necessary to implement as early as possible about PHBS education and prevention of covid-19 so that children avoid the disease covid-19. The Purpose. To determine the effect of education on clean and healthy living behavior (PHBS) on the behavior of preventing COVID-19 in school-age children Method. This study is a post-test, pre-post test and the static group comparison design research to determine the effect of clean and healthy living behavior education (PHBS) on covid-19 prevention behavior in school-age children, the results of the study using Paired T-Test Results. Mean before education 12,2750 and after education 15.1000, mean differences -2,82500, std deviation 2,70695 . Based on the value of the mean difference (mean differences) is negative, namely -2,82500, it can be interpreted that the result after being given education is higher than before being given education, with sig. (2-tailed) p value = 0,001. The Conclusion. PHBS behavior education is significantly effective for improving Covid-19 prevention behavior Keywords PHBS Education, Covid-19 prevention behavior in children